Psychosocial Determinants Contributing to the Exacerbation of Symptoms in Heart Failure Patients - Eslyano Herdan Pratama; Beti Kristinawati (Indonesian Journal of Global Health Research, 2026)
Heart failure is a chronic disease characterized by a decline in heart function, causing physical symptoms such as shortness of breath, edema, and fatigue, as well as psychological symptoms such as anxiety and depression. It is more common in low-income countries and is closely related to psychosocial factors such as anxiety, depression, social support, and economic status, which affect the severity of symptoms and treatment adherence. Although mental health and social support can improve patients' quality of life, previous studies have not provided significant evidence regarding psychosocial determinants that exacerbate heart failure symptoms. Therefore, this study aims to identify psychosocial factors contributing to worsening symptoms in heart failure patients. This study used a descriptive quantitative design with purposive sampling of 317 respondents from a total population of 1,528 heart failure patients at the Sebelas Maret University Hospital Heart Clinic from February to April 2025, using the HADS (α=0,85 for anxiety; α=0,80 for depression), MS-PSS (α=0,85), and ESAS (α=0,78) instruments with logistic regression analysis. The results showed that the majority of respondents were aged 40–59 years, male, and had hypertension as a comorbidity, with 51.4% experiencing worsening symptoms, and anxiety was found to be the most significant determinant (p = 0.0001; OR = 3.043). These findings confirm that psychosocial factors play an essential role in the worsening of heart failure symptoms, with anxiety being the main factor that significantly increases risk compared to depression or low social support.